1973
DOI: 10.1002/jsfa.2740240307
|View full text |Cite
|
Sign up to set email alerts
|

The aleurone layer of wheat. III. Isolation and scanning electron microscope examination of the layer and of its component parts

Abstract: Methods have been devised for the isolation from wheat bran of (i) large fragments of aleurone layer, (ii) contents of aleurone cells, (iii) aleurone cell walls and (iv) aleurone granules. The structure of these preparations has been examined using the scanning electron microscope. Dimensions were generally smaller than those reported by workers using conventional microscopy of wheat sections, since. the latter were swollen by aqueous mounting. Although the polygonal prismatic cells varied in size and shape, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

1973
1973
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 3 publications
1
4
0
2
Order By: Relevance
“…Fiber A (wheat aleurone) revealed particles rich in aleurone layer. It is worth noting the uniformity of fiber A particles, which could be an indication of high purity of the aleurone fiber, as previously shown (Stevens 1973; Harris et al 2005). Fiber B (wheat bran), however, showed smaller bran particles with some fragments of starch granules.…”
Section: Resultssupporting
confidence: 79%
“…Fiber A (wheat aleurone) revealed particles rich in aleurone layer. It is worth noting the uniformity of fiber A particles, which could be an indication of high purity of the aleurone fiber, as previously shown (Stevens 1973; Harris et al 2005). Fiber B (wheat bran), however, showed smaller bran particles with some fragments of starch granules.…”
Section: Resultssupporting
confidence: 79%
“…2), or multilayered in barley, rice, and oats (Stone, 1985). In wheat, the diameter of aleurone cells is 20-75 µm (Stevens, 1973), and the aleurone layer represents ∼50% of the wheat bran. The aleurone cell is composed of the cytoplasm or intracellular medium, surrounded by thick nonlignified cell walls, which represent ∼35% of the cell volume (Fulcher et al, 1972), and more than 40% of the layer in mass (Hemery et al, 2009a).…”
Section: The Aleurone Layer Within the Whole Grainmentioning
confidence: 99%
“…It was especially observed that the easiest bran to free from adherent endosperm during the milling had the smoothest aleurone-endosperm profiles (Crewe and Jones 1951). Later, scanning electron microscope examination of isolated fragments of aleurone layer showed that its outer face, adjacent to the nucellar epidermis, presented a flat surface, whereas its inner face appeared more irregular with a succession of convex and concave cells and intercell depressions (Stevens 1973). Aleurone irregularity could favor adhesion or simply entangle residual fragments of starchy endosperm and thus influence the extraction rate of semolina.…”
Section: Influence Of Structural Characteristics Of Aleurone Layer Onmentioning
confidence: 99%